Aplikasi Manajemen Surat Masuk dan Surat Keluar Berbasis Mobile di Perum Bulog Subdivre Dumai - Rahmat Hidayatullah; Vivi Asmawati; Deasy Wahyuni (JISKA (Jurnal Informatika Sunan Kalijaga), 2020)
Letters are a means of communication used to convey written information by one party to other parties both related to business and non-business activities. Handling and managing letters, both incoming and outgoing letters at the Perum Bulog Subdrivre Dumai are still done manually. Where incoming and outgoing letters are recorded in the agenda book. Therefore, a mobile-based incoming and outgoing mail management application was designed at the Perum Bulog Subdivre Dumai using a laravel framework with the Hypertext Preprocessor (PHP 7.1.3) programming language and JavaScript. For mobile devices built using the Native React Framework. The application can facilitate the information of incoming mail to the leadership, facilitate the allocation of follow-up and disposition of incoming mail in the relevant fields, facilitate approval of outgoing letters to the leadership and accelerate the search for data.